2023
DOI: 10.1021/accountsmr.2c00261
|View full text |Cite
|
Sign up to set email alerts
|

Exploration and Insight of Dynamic Structure Evolution for Electrocatalysts

Abstract: Conspectus Electrochemical energy technology is crucial for transitioning from fossil fuels to renewable energy sources due to its clean, efficient, and sustainable nature. Electrocatalysts are capable of maximizing energy conversion efficiency in a practical electrochemical energy technology by accelerating the charge transfer at the electrode–electrolyte interface, in which the structure and composition of the electrocatalyst directly determine the catalyst performance. Therefore, advanced electrocatalysts p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…5f). 50 During the OER process (1.00 to 1.80 V vs. RHE), the main peaks of CFBN-3 remained, which confirmed that the crystalline layer has a certain degree of anti-surface reconstruction (anti-SRC). 51 The presence of a stable crystalline phase indicated that exf-NiPS 3 acts as an active substrate, providing strong support.…”
Section: Resultsmentioning
confidence: 71%
“…5f). 50 During the OER process (1.00 to 1.80 V vs. RHE), the main peaks of CFBN-3 remained, which confirmed that the crystalline layer has a certain degree of anti-surface reconstruction (anti-SRC). 51 The presence of a stable crystalline phase indicated that exf-NiPS 3 acts as an active substrate, providing strong support.…”
Section: Resultsmentioning
confidence: 71%
“…The design of long-lifetime and high-durability electrocatalysts for low-temperature CO 2 RR remains to be an ongoing area. Compared to high-temperature CO 2 RR, the stability of electrocatalysts for low-temperature CO 2 RR still suffers from relatively rapid structural evolution and performance degradation mainly due to the complicated reaction environment . The development of highly stable and corrosion-resistant electrocatalysts is imperative to advancing low-temperature CO 2 RR utilization.…”
Section: Prospects Of Co2 Electrolysismentioning
confidence: 99%
“…The structural evolution of catalysts under acidic conditions could be explicated by operando characterizations and isotope labeling tests, which can precisely identify the active sites and help to understand the charge transfer process of catalysts. 282 Moreover, DFT calculations can help to elucidate the possible reaction pathways by predicting the thermodynamics of intermediates based on the information gained from operando measurements. DFT results are related to the applied physical models and computational parameters; therefore, how to precisely model the real operating environments and rationally correlate the catalytic features with electrochemical performances is significant for impactful DFT investigations.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%